Bacteria associated with contact lenses among asymptomatic students wearers of university of Tripoli, Libya - Abir Ben Ashur (The Libyan Journal of Science, 2022)
The use of contact lenses without special precautions and sterilization procedures results in keratitis and other eye infections. In Libya, contact lenses are common, and many people are unaware of rieht proper care and sterilization measures. The study aimed to evaluate the bacterial contamination in contact lenses among university students and determine the level of awareness regarding contact lens hygiene. This cross-sectional study was carried out from April to August 2022 on 50 medical students of the Faculty of Medical Technology at Tripoli University of Tripoli city Libya, who are asymptomatic and wear contact lenses. A questionnaire on personal information, contact lens wear, and lens handling procedures was distributed. The samples were taken from the lens with sterile swabs and quickly cultured, and the organism is identified using appropriate biochemical tests. and antimicrobial susceptibility tests by standard protocols. A total of 46 bacterial isolates were identified from 50 samples and the remaining 4 samples were found to have no growth. The common isolates were Pseudomonas aeruginosa 20 (83.3%), followed by Staphylococcus aureus 10 (45.5 %), Staphylococcus epidermidis 8 (36.4%), Escherichia coli 3 (12.5%), Streptococcus viridans 2 (9.1%), Streptococcus agalactiae 1 (4.5%), and Streptococcus pneumoniae 1 (4.5%), Haemophilus influenza 1 (4.2%). Our findings demonstrate that contact lenses are highly contaminated with bacterial strains and that could be due to improper care of contact lenses by wearers. Increasing awareness is crucial to avoid any identified risk factors to the eyes that can occur from organisms’ contamination. Regular standard protocols lens care for the usage is, therefore, are essential.